Anti-inflammatory and antidiabetic activity of ethanolic extracts of Sterculia villosa barks on Albino Wistar rats - Md. Kamal Hossain, Md. Akhtaruzzaman Prodhan, A. S. M. Ibnul Hasan Even, Helal Morshed, Md. Monir Hossain (Journal of Applied Pharmaceutical Science)
Ethanolic extract of Sterculia villosa barks were studied for anti-inflammatory and antidiabetic activity. The acute oral toxicity showed that the ethanolic extract of S. villosa barks was safe until 4000mg/kg body weight and no macroscopical organ abnormalities were observed in acute oral models. The investigations on Albino (Wistar) rats at dosage of 100, 200 and 400 mg/kg of ethanolic extract of Sterculia villosa barks were made for aniti-inflammatory action by using carrageenan induced paw edema and cotton pellete granuloma technique. The results of the study suggested significant dose dependent activity of extracts as compared to control group for both acute and chronic inflammation. Ethanolic extract also showed significant antidiabetic activity at dose dependent manner compared to diabetic untreated group.
Keywords: Sterculia villosa barks,anti-inflammatory activity,antidibatic activity,carrageenan induced paw edema,cotton pellet granuloma,Alloxan.